Incidence of Fusarium spp. in corn: from plant to grain (Research, Society and Development, 2021)
It is difficult to establish the moment when phytopathogenic fungi affect the grains while still in the field, being Fusarium one of the main fungi in the corn crop that causes loss of productivity and quality of the grains produced. Thus, the aim of this study was to quantify the incidence of Fusarium spp. in corn crop as a function of phenological stages, in different hybrids and planting times. The incidence of the fungus on leaves, tassels and ears was evaluated by the indirect isolation method of phytopathogenic fungi. Material collections were carried out at stages V7, VT, R1, R3, R4, R6 and pre-harvest, in the planting times December to March (1st harvest) and March to June (2nd harvest). The hybrids evaluated in the 1st crop were ADV 9275 PRO and ALWAYS 20A30 and in the 2nd crop, RB9110PRO2, 2B512PW, 2B633PW and 2A401PW. The hybrids showed the same incidence trend of Fusarium spp. in leaves and tassels in both seasons. The reproductive stages showed a high incidence of Fusarium spp. in all parts of the plant evaluated, and in the R6 and pre-harvest stages the highest fungal incidence was observed, regardless of the hybrid and planting time. The hybrids ALWAYS 20A30, 2A401 PW and 2B512 PW had a higher incidence of Fusarium spp., while the material RB9110 PRO2 showed greater resistance to the fungus. In the 1st crop, the hybrids showed a higher incidence of the phytopathogen in the ear, while in the 2nd crop there was a higher incidence in the leaf and tassel.